2015
DOI: 10.5395/rde.2015.40.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management with intentional replantation on a tooth with palato-radicular groove

Abstract: A palato-radicular groove (PRG) is a developmental anomaly primarily found in the maxillary lateral incisors. It is a potential communication path between the root canal and the periodontium that decreases the survival prognosis of the affected tooth, therefore compromising the stability of the dental structure in the oral cavity. The aim of this case report is to present an original technique where a PRG was treated by means of intracanal disinfection, PRG sealing with glass ionomer, replantation with intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Several PGG cases have been reported recently. Clinically, patients with a pathologic lesion related to PGG often complain of dull intermittent 27 28 or acute pain, 22 29 mobility of the teeth, 30 31 32 pain on percussion, 27 pus discharge, 29 30 31 33 sinus tract formation ( Figure 1a ), 15 32 33 and gingival swelling. 22 They can also present with no symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several PGG cases have been reported recently. Clinically, patients with a pathologic lesion related to PGG often complain of dull intermittent 27 28 or acute pain, 22 29 mobility of the teeth, 30 31 32 pain on percussion, 27 pus discharge, 29 30 31 33 sinus tract formation ( Figure 1a ), 15 32 33 and gingival swelling. 22 They can also present with no symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In cases with an extensive groove area, some authors have reported successful treatment outcomes with intentional replantation. 29 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Schwartz and coworkers in 2006 described a combined endoperiodontal treatment that was complicated by the complex root canal anatomy [5]. Other authors proposed the extraction, endodontic treatment, and sealing of the groove using composite resin or glass ionomer cement and subsequent replantation of the affected teeth [11, 27]. Al-Hezaimi and coworkers associated intentional extraction and replantation with EMD application to treat residual bone defect [28].…”
Section: Discussionmentioning
confidence: 99%
“…27 GIC used in the present case showed similar results with Forero-López et al, who reported the new technique sensitive procedure which involved sealing PRG with GIC, replantation with intentional horizontal 180 degree rotation of tooth and aesthetic veneer for restoring tooth morphology. 28 But Naik et al and Zucchelli et al have used biodentine and flowable composite, respectively. 29 30 Zucchelli et al also have demonstrated successful results by using papilla amplification flap and Emdogain (Institut Straumann, Waldenburg, Switzerland) which is unique of this case.…”
Section: Discussionmentioning
confidence: 99%